Health promotion nursing activities for the elderly with chronic obstructive pulmonary disease: A cross-sectional study - Soodabeh Lotfi Palangy; Fatemeh Ghaffari; Zahra Fotokian; Ali Zabihi (Tehran University of Medical Sciences, 2021)
Background & Aim: Health promotion nursing activities for the elderly with COPD is different in various health care structures, and research in this area can help to identify the existing knowledge gap. The aim of this study was to determine health promotion nursing activities for the elderly with COPD. Methods & Materials: This descriptive, cross-sectional study was conducted in 2020. A total of 180 nurses working in teaching hospitals affiliated to Mazandaran University of Medical Sciences were selected using the convenience sampling method. Data collection tools included a demographic questionnaire and a researcher-made questionnaire on health promotion nursing activities for the elderly with COPD. The data was analyzed through the SPSS software version 18 using t-test, ANOVA and multivariate regression. Results: The mean age of nurses was 34.58±8.05 years, 84.4% were female and 70.6% were married. The mean score of health promotion nursing activities was 197.10±37.90. Among the dimensions related to health promotion activities, "drugs/smoking cessation" (34.4%) and "self-empowerment" (32.8%) had the lowest frequency. There was a significant relationship between health promotion nursing activities with the work place (P=0.034), age (P<0.001), gender (P=0.022) and marital status (P=0.014). Conclusion: The health promotion nursing activities for the elderly with COPD was above moderate levels. In-service training programs and internal conferences are needed especially in the area of ​​counseling behaviors and smoking cessation in order to improve the professional competency of nurses.